Gender identity and economic decision making - Anne Ardila Brenøe; Zeynep Eyibak; Lea Heursen; Eva Ranehill; Roberto A. Weber (Lund University, School of Economics and Management, Department of Economics, 2024)
Economic research on gender gaps in preferences and economic outcomes has focused on variation with respect to sex-a binary classification as either a "man" or "woman." We validate a novel and simple measure of self-reported continuous gender identity (CGI) and explore whether gender identity correlates with variation in economic decisions and outcomes beyond the relationship with binary sex. We use four datasets (N=8,073) measuring various dimensions of economic preferences and educational and labor market outcomes for which prior research has documented gaps between men and women. Our analysis rejects the null hypothesis that CGI has no relationship with behaviors and preferences beyond the relationship with binary sex, particularly for men, and suggests that incorporating self-reported measures of gender identity may have value for understanding gender gaps and for targeting policy. However, when considering specific domains, the relationships vary in statistical significance and are often small.
Keywords: J16; J2; C91; 330; Gender identity; non-binary gender; economic preferences; economic outcomes